Inovasi Pengolahan Buah Salak Sebagai Produk Kuliner dan Oleh Oleh Khas di Desa Wisata Sibetan - Hardina Hardina; I Gusti Made Iwan Dusanta Martadjaya; Ngakan Putu Sudiarta (JURNAL GASTRONOMI INDONESIA, 2021)
Sibetan Tourism Village is the center of salacca plantation in Bali. Various processed products from salacca fruit produced by agro-tourism in Sibetan Village become special culinary and souvenirs that can improve the community's economy. However, in it’s journey, typical culinary products and souvenirs are very difficult to sell outside the region. The purpose of the study was to determine the condition of salacca fruit farming in Sibetan Tourism Village and analyze the innovations made in processing snake fruit as culinary products and typical souvenirs of Sibetan Tourism Village. The research method used qualitative method. The results showed that the condition of snake fruit farming consisted of approximately 9 types of salacca fruit and 5 types of agro-tourism. Salacca Fruit processing innovations that are most in demand by tourists are snake fruit wine. The packaging of products has followed the trend of souvenirs packaging. The marketing has utilized social media such as Instagram, Facebook, You Tube and through TV media. The management of the Sibetan Tourism Village has also begun to expand its network of cooperation with the Godevi marketplace.